2022
DOI: 10.3390/ijms232213794
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cells in Clinical Cell Transplantation: Focusing on Induced Pluripotent Stem Cell-Derived RPE Cell Therapy in Age-Related Macular Degeneration

Abstract: Human pluripotent stem cells (PSCs), including both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), represent valuable cell sources to replace diseased or injured tissues in regenerative medicine. iPSCs exhibit the potential for indefinite self-renewal and differentiation into various cell types and can be reprogrammed from somatic tissue that can be easily obtained, paving the way for cell therapy, regenerative medicine, and personalized medicine. Cell therapies using various iPSC-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We found that flavonoid glycoside can significantly reduce the number of retinal leakage, improve the retinal thickness and increase the retinal A wave and B wave. These results indicate that flavonoid glycoside have a very significant effect on the recovery of retinal injury [26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 62%
“…We found that flavonoid glycoside can significantly reduce the number of retinal leakage, improve the retinal thickness and increase the retinal A wave and B wave. These results indicate that flavonoid glycoside have a very significant effect on the recovery of retinal injury [26][27][28][29][30] .…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, can be individually separated manually, however, it requires significant manpower [9,10]. The optic nerve is well known not to regenerate, and the repair of damaged optic nerves using iPSC-RGCs remains a hurdle in clinical transplantation [49].…”
Section: Discussionmentioning
confidence: 99%
“…iPSCs are generated by reprogramming adult somatic cells to a pluripotent state, circumventing the ethical concerns associated with ESCs ( Figure 1 ) [ 94 ]. As with ESCs, iPSCs have the ability to differentiate into various cell types and have shown promise in preclinical studies for SCI treatment [ 95 , 96 ]. iPSC-derived neural cells have been used to replace lost neurons, promote axonal regeneration, and provide neurotrophic support, contributing to functional recovery in animal models of SCI [ 97 , 98 ].…”
Section: The Potential Of Different Stem Cell Typesmentioning
confidence: 99%